Hg0-temperature-programmed surface reaction and its application on the investigation of metal oxides for Hg0 capture. (1st October 2016) - Zhao, Haitao; Yang, Gang; Gao, Xiang; Pang, Chengheng; Kingman, Sam; Lester, Edward; Wu, Tao
Graphical abstract: Highlights: A novel Hg 0 -TPSR was developed for the rapid evaluation of Hg 0 capture materials. Non-noble metal oxides as candidate Hg 0 capture materials were rapidly evaluated. Hg 0 capture performance of these metal oxides was significant promoted by Mo. Abstract: Because of the detrimental impacts on the biological systems and human being's health, there is an urgent need for the development of novel materials for the removal of mercury emitted as a result of fossil fuel consumption. In this study, a novel Hg 0 -Temperature-Programmed Surface Reaction (Hg 0 -TPSR) was developed for the rapid evaluation of candidate Hg 0 capture materials. A suite of non-noble metal oxides were studied using the Hg 0 -TPSR together with some qualitative and quantitative methods. It was found that Mn-O, Cu-O, Ce-O, Co-O, Ni-O and Fe-O showed better performance in Hg 0 capture among the metal oxides studied. When Mo was added as the promoter, the performance of these metal oxides in mercury capture was significantly enhanced: the Hg 0 capture potential of Mo-promoted metal oxides was improved; the activation energy was reduced; and the effective temperature window was broadened. Among these Mo-promoted metal oxides, Mn-Mo-O, Cu-Mo-O, Ce-Mo-O and Co-Mo-O materials showed good potential to be used as the non-carbon-based materials for Hg 0 capture. It is also demonstrated that the Hg 0 -TPSR method is an effective and efficient approach for the rapid evaluation of novel materials for Hg 0 capture.